Comparative assessment of some benzodiazepine drugs based on Density Functional Theory, molecular docking, and ADMET studies - Uzzaman, Monir; Ahsan, Amrin; Uddin, Mohammad Nasir (European Journal of Chemistry, 2021)
Benzodiazepines are widely used to treat anxiety, insomnia, agitation, seizures, and muscle spasms. It works through the GABAA receptors to promote sleep by inhibiting brainstem monoaminergic arousal pathways. It is safe and effective for short-term use, and arises some crucial side effects based on dose and physical condition. In this investigation, physicochemical properties, molecular docking, and ADMET properties have been studied. Density functional theory with B3LYP/6-311G+(d,p) level of theory was set for geometry optimization and elucidate their thermodynamic, orbital, dipole moment, and electrostatic potential properties. Molecular docking and interaction calculations have performed against human GABAA receptor protein (PDB ID: 4COF) to search the binding affinity and effective interactions of drugs with the receptor protein. ADMET prediction has performed to investigate their absorption, metabolism, and toxic properties. Thermochemical data suggest the thermal stability; the docking result predicts effecting bindings and ADMET calculation disclose non-carcinogenic and relatively harmless phenomena for oral administration of all drugs.